Efficiency Aspects of Orientation Estimation with Optical Flow on Mobiles - Kundra, Laszlo; Ekler, Peter (2015 4th Eastern European Regional Conference on the Engineering of Computer Based Systems, 2015)
In this paper techniques for reliable orientation estimation on Android-based devices are investigated in the aspect of processing demand. In terms of reliability, an optical flow based sensor fusion method is proposed. With a well detailed measurement configuration, the results are shown in the aspect of processor load and different frame rate for both synchronous and asynchronous processing.